The nematode signaling molecule ascr#18 induces prepenetration defenses in wheat against a leaf rust fungus - Kamboj, Akshita; Thielmann, Jennifer; Delfan, Saba; Kloppe, Tim; Schulz, Philipp; Manohar, Murli; Schroeder, Frank C.; Klessig, Daniel F.; Kogel, Karl-Heinz; Justus Liebig University Giessen (My University, 2024)
Leaf rust, caused by the pathogenic biotrophic rust fungus Puccinia triticina (Pt), is one of the most destructive wheat diseases worldwide; its negative impact on crop yields is exacerbated by increasing temperatures due to climate change. Ascarosides are nematode pheromones that induce resistance to microbial pathogens and pests in a wide range of crops, making them valuable components in biocontrol scenarios. We investigated the effect on infection of various wheat (Triticum aestivum) genotypes with the virulent Pt race 77W × R by ascr#18, the major ascaroside secreted into the rhizosphere by plant-parasitic nematodes. Spraying the leaves with ascr#18 24 h before inoculation with fungal uredospores slowed disease development and resulted in a reduction of the number of rust pustules on treated compared to untreated leaves. Dose–response analysis over the nano- and micromolar range revealed a broad optimum concentration down to 0.01nM ascr#18. Microscopic analysis showed very early arrest of the fungus at the appressorial stage, with associated enhanced local accumulation of H2O2 and abortive stoma penetration. Similarly, ascr#18 also induced strong resistance to Pt race PKTTS, confirming its race-unspecific biocontrol activity. The results of this study are consistent with and extend previous research that has shown that ascr#18 activates plant immunity and thus protects plants from pathogens even at very low doses.
Keywords: ddc:630